On shoulders of giants: 70 years of science for conservation published in Wildfowl - Rees, Eileen C.; Fox, Anthony D. (Wildfowl, 2020)
This 70th annual issue of the Wildfowl & Wetlands Trustâ€™s scientific journal Wildfowl, which commenced life as the First Annual Report of the Severn Wildfowl Trust in 1948, provides a timely opportunity to review and celebrate the wealth of knowledge and pioneering research published in its pages over the decades. During this time it has disseminated the results of scientific studies undertaken globally on wildfowl and their wetland habitats, providing an invaluable source of information required to understand and conserve these species.Â  In this retrospective editorial, we therefore review the heritage and evolution of the journal, its core role within the Wildfowl & Wetlands Trust (publisher of the journal), major papers published through its history, and recent advances in recognition of the journal in the 21st century.